(untitled) (Bulletin KNOB, 1997)
In the Topographical Atlas of the municipal archives of Utrecht there is a unique collection of drawings. They were made by orphan boys from the Reformed orphanage on the responsibility of art teacher Arnoldus Koopman who was employed there from 1766 to 1805. A quarter of the 296 preserved drawings fall under the scope of architecture, of which one-third concerns accurate studies of columns and two-thirds are drawings of stairwells, roof timbers and roof constructions. The greater part of them was signed and unfortunately just a small part of them was dated. On the basis of these datings it is to be assumed that most of them were made during the last period of their makers’ stay in the orphanage, which they usually left around the age of 24. Apart from these there are twelve drawings on various subjects, probably chiefly from the period between 1770 and 1780. These are the most interesting ones. They include, for instance, designs for town halls and country estates, for domed summerhouses and garden houses, as well as a beautiful sketch of an organ front. There often was a connection with the trade for which the maker was being educated, frequently the trade of carpenter, but also of decorative painter (a ceiling), cabinetmaker (the organ) or stained-glass artist (garden houses with a lot of glass). From a stylistic point of view the designs are rather conservative in character; the new neo-Classicism of those days is hardly noticeable.